2014
DOI: 10.1039/c4dt00481g
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor chemistry in the main group

Abstract: This Perspective article summarizes recent progress from our laboratory in the isolation of reactive main group species using a general donor-acceptor protocol. A highlight of this program is the use of carbon-based donors in combination with suitable Lewis acidic acceptors to yield stable complexes of parent Group 14 element hydrides (e.g. GeH2 and H2SiGeH2). It is anticipated that this strategy could be extended to include new synthetic targets from throughout the Periodic Table with possible applications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 110 publications
0
59
0
3
Order By: Relevance
“…Notably, the transition metal iminoboryl systems were found to be stable against oligomerization, yet reactive towards a variety of substrates. [6,7] In recent years, it has been shown that stable singlet carbenes [8] can be used, in place of transition metals, to not only stabilize a variety of highly reactive species, [9] but also to activate small molecules and enthalpically strong bonds. [10,11] Herein, we report that a singlet cyclic (alkyl)(amino)carbene (CAAC) [12] reacts with bis(trimethylsilyl)dihaloboranes, and allows for the preparation of room-temperature-stable iminoboryl-carbene adducts.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the transition metal iminoboryl systems were found to be stable against oligomerization, yet reactive towards a variety of substrates. [6,7] In recent years, it has been shown that stable singlet carbenes [8] can be used, in place of transition metals, to not only stabilize a variety of highly reactive species, [9] but also to activate small molecules and enthalpically strong bonds. [10,11] Herein, we report that a singlet cyclic (alkyl)(amino)carbene (CAAC) [12] reacts with bis(trimethylsilyl)dihaloboranes, and allows for the preparation of room-temperature-stable iminoboryl-carbene adducts.…”
Section: Introductionmentioning
confidence: 99%
“…Some remarkable examples of the application of this strategy have been the subject of a recent Perspective article, and most feature the use of N-heterocyclic carbene stabilized acceptors behaving as donors. 47 Analogous Lewis-basic behaviour for phosphine stabilized complexes has only been reported for a few acceptor elements. In group 14, the most diverse examples are from the coordination chemistry of phosphonium ylides and double ylides (carbodiphosphoranes).…”
Section: Coordination and Oxidation Of Lone Pair Bearing Acceptor-cenmentioning
confidence: 98%
“…Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands. In particular, for the heavier carbon analogue silicon, a plethora of studies reported new low-valent compounds in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the chemistry of silylene base adducts has already been carefully developed [14,[26][27][28][29][30][31][32][33][34][35][36]. Before these findings, silyliumylidene ions, cationic Si(II) species were found to be promising as similar versatile Lewis amphiphiles [37,38].…”
Section: Introductionmentioning
confidence: 99%